Community Based Tourism dalam Pengelolaan Desa Wisata Giriloyo, Wukirsari, Imogiri, Bantul - Suwarjo, Suwarjo (Universitas Widya Mataram, 2019)
The results of study showed that community-based community in Giriloyo Tourism Village can be used for all community of batik artisans community who joined in paguyuban batik. Community agility from the stages of planning, evaporation, to activities. Forum meetings from hamlet level, batik community to tourist village become a forum for the community to convey aspirations and campaigns-inspiring activities.Â To motivate the community in Giriloyo Tourism Village, the following suggestions are offered: 1) the need for optimization of community meeting vessels to explore the potentials of interest for batik. Special tours special outbound and traditional culinary; 2) to increase the interest of the young generation of batik handicrafts in Giriloyo Tourism Village, can organize annual event with batik and staining pattern creations. Competition can be done in groups and there is no relationship that can be established relationships and close cooperation between adolescents.